Concurrent oxytocin with dinoprostone pessary versus dinoprostone pessary in labour induction of nulliparas with an unfavourable cervix: a randomised placebo-controlled trial - Tan, P.C.; Valiapan, S.D.; Tay, P.Y.S.; Omar, S.Z. (Elsevier, 2007)
Objective To compare concurrent oxytocin with dinoprostone pessary versus dinoprostone pessary in labour induction for nulliparas with an unfavourable cervix. Design A randomised double-blind study. Setting University Malaya Medical Centre, Malaysia. Population Nulliparas at term with intact membranes, Bishop score <= 6 and admitted for labour induction. Methods All women received 3 mg dinoprostone pessary for labour induction. Those randomised to the oxytocin arm received oxytocin infusion started at 1 mu/minute and doubled every 30 minutes to a maximum 16 mu/minute. Women assigned to placebo received identical volume of saline infusion. After 6 hours, infusion was stopped and vaginal reassessment performed to guide further management. Main outcome measures Primary outcome was vaginal delivery within 24 hours. Results Concurrent oxytocin infusion with dinoprostone pessary did not significantly increase vaginal delivery rate within 24 hours (48.6 versus 35.9; P = 0.07, relative risk RR 1.4 95% CI 1.0-1.9). It reduced the requirement for repeat dinoprostone (37.1 versus 61.2%; P = 0.001, RR 0.61 95% CI 0.45-0.81) and improved maternal satisfaction with the birth process (median score of 3 versus 5 on a 10-point visual analogue scale, P = 0.007). Caesarean rates were not different (41.9 versus 44.7%, P = 0.52). Conclusions Labour induction with concurrent oxytocin infusion and vaginal dinoprostone could be considered for nulliparas with an unfavourable cervix. Larger studies are needed.